2022
DOI: 10.3390/jcm11072018
|View full text |Cite
|
Sign up to set email alerts
|

Novel Mode of Near-Infrared Spectroscopy as a Continuous Cerebral Physiological Monitoring Device during Cardiopulmonary Resuscitation: Four Case Reports

Abstract: Background: NIRO-Pulse is a novel mode of near-infrared spectroscopy that can be used to visually evaluate cerebral perfusion during cardiopulmonary resuscitation (CPR), providing real-time feedback as to the quality of the CPR. The aim of this report was to describe the several representative cases of NIRO-Pulse for physiological monitoring during CPR. Methods: We present several cases from out-of-hospital cardiac arrest (OHCA) patients for whom NIRO-Pulse was attached to the forehead after hospital arrival. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…SctO 2 provided by NIRS is a highly anticipated noninvasive physiological monitor for assessing the quality of CPR and predicting outcomes [21]. Prior studies indicated that higher SctO 2 values are associated with a greater likelihood of achieving ROSC and favorable neurological outcomes [21][22][23][24][25]. Our investigation revealed that in Cases 1 and 2, which had higher MAP, ROSC was reached after increased SctO 2 values.…”
Section: Discussionmentioning
confidence: 56%
“…SctO 2 provided by NIRS is a highly anticipated noninvasive physiological monitor for assessing the quality of CPR and predicting outcomes [21]. Prior studies indicated that higher SctO 2 values are associated with a greater likelihood of achieving ROSC and favorable neurological outcomes [21][22][23][24][25]. Our investigation revealed that in Cases 1 and 2, which had higher MAP, ROSC was reached after increased SctO 2 values.…”
Section: Discussionmentioning
confidence: 56%